Mathematical aspects of the use a lot of alternative rules is in tasks of channel encoding - Юдін, О. К.; Чунарьова, А. В. (Problems of Informatization and Control, 2009)
An analysis is conducted a lot of alternative rules of decision-making. The model of decision procedures is built for determination of possibility of the use a lot of alternative rules of decision-making is in the tasks of the channel encoding. The thresholds of decision-making with the purpose of reliable renewal complete code construction are set